Synthesis of N-Alkyl-Carbazole Derivatives as 5-HT7R Antagonists - Kim, Youngjae; Yeom, Miyoung; Lee, Soyeon; Tae, Jinsung; Kim, Hak Joong; Rhim, Hyewhon; Seong, Jihye; Choi, Kyung Il; Min, Sun-Joon; Choo, Hyunah (대한화학회, 2018)
We designed and synthesized a series of N-alkyl-carbazoles with different alkyl chains and amine moieties, and biological evaluation was performed to discover novel 5-HT7R antagonists. Among 27 synthesized compounds, 20, 21, 23, and 24 showed excellent binding affinities to 5-HT7R (K-i = 65, 64, 55, and 31 nM, respectively), and good selectivity profiles over other serotonin receptors. In functional assays, those compounds showed weak antagonistic activities against 5-HT7R. In particular, the compound 24, 2-(4-(5-(9H-carbazol-9-yl)pentyl)piperazin-1-yl)phenol, could be considered as a potent and selective 5-HT7R ligand with weak antagonistic effect. From the molecular docking study, the aromatic hydroxyl group in 24 was shown to play an important role in binding to 5-HT7R through a hydrogen bonding interaction with Asp142 in the ligand binding pocket of 5-HT7R.